Embracing Ambiguity: The intersection of biology, music, and art in secondary school teaching for student creativity - Ausman, Tasha; Mandel, Travis (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2020)
In these conversational field notes, two teachers reveal their experiences with creativity in contexts where students are encouraged to dwell in spaces of ambiguity and vulnerability in learning.  Using anatomy to inform music pedagogy empowers students to work through metaphor-rich instruction in order to develop a grounded approach to artistic interpretation, while using fine art in the science classroom allows students of anatomy to explore the artistic possibilities of imagination in relation to the human body. In both cases, the crisscrossing of pedagogical lines from biology into music and music into art helped to transform students’ relationships with ambiguity from being negative and closed-off, to positive and constructive.